Analisis Ekualisasi Pajak Terhadap Kepatuhan Perpajakan pada PT. XYZ - Fitri Nadia Salsabila; Oryza Tannar (Jurnal Riset Manajemen dan Akuntansi, 2026)
This study aims to analyze the effect of implementing the tax equalization method on tax compliance at PT. XYZ, a company operating in the manufacturing sector. The research employs a descriptive qualitative approach with data collected through financial report documentation, tax return (SPT) records, and semi-structured interviews with tax and finance staff during the period of January to June 2025. The results indicate that the routine and systematic application of tax equalization can identify significant discrepancies between financial reports and tax returns, primarily arising from vehicle rental transactions, promotional expenses, export sales, and subcontractor services that were not properly reported. Consequently, the company can correct its accounting records and revise its tax returns before a tax audit occurs. The study concludes that tax equalization is proven effective as an internal control tool that enhances corporate tax compliance by enabling early detection of discrepancies between commercial and fiscal data, fostering internal transparency, and minimizing the risk of tax penalties. The implication of this research is that manufacturing companies should integrate the tax equalization system as part of their periodic internal control, supported by continuous training for finance and tax teams to improve their understanding of tax regulations, as well as the implementation of an integrated accounting information system connected with the tax system to prevent recurring reporting discrepancies.